Chroma Noise Reduction in DCT Domain Using Soft-Thresholding. (9th January 2011) - Buemi, Antonio; Bruna, Arcangelo; Mancuso, Massimo; Capra, Alessandro; Spampinato, Giuseppe
Abstract : The chroma noise effect seriously reduces the quality of digital images and videos, especially if they are acquired in low-light conditions. This paper describes the DCT-CNR (Discrete Cosine Transform-Chroma Noise Reduction), an efficient chroma noise reduction algorithm based on soft-thresholding. It reduces the contribution of the DCT coefficients having highest probability to be corrupted by noise and preserves the ones corresponding to the details of the image. Experiments show that the proposed method achieves good results with low computational and hardware resources requirements.